2008
DOI: 10.1111/j.1610-0387.2008.06720.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of glucose/insulin metabolic alterations in men with multiple skin tags on the neck

Abstract: Multiple skin tags appear associated with abnormalities in glucose/insulin metabolism. Clinical and metabolic glucose/insulin characteristics of men with multiple (8 or more) skin tags on the neck were compared with a control group with few or none. Both groups were divided in two subgroups according to normal or abnormal laboratory findings. In the study subgroup with normal laboratory findings the number of skin tags varied from 8-33, whereas in those with abnormal laboratory findings the range was 9-65. Eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 9 publications
(10 reference statements)
2
36
0
12
Order By: Relevance
“…This finding could be explained by the work of Sudy et al, [5], who demonstrated that multiple skin tags were more sensitive than acanthosis nigricans in identifying alterations in the glucose/insulin metabolism and that they should raise suspicion of insulin resistance or hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could be explained by the work of Sudy et al, [5], who demonstrated that multiple skin tags were more sensitive than acanthosis nigricans in identifying alterations in the glucose/insulin metabolism and that they should raise suspicion of insulin resistance or hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in estrogen levels and trophic hormones such as insulin-like growth factor-1 (IGF-1) and epidermal growth factor [5], as well as increased mast cell count [6], are involved in the genesis and development of skin tags. Various skin conditions are associated with insulin resistance including pseudocanthosis nigricans, hirsutism, acne, hidradenitis suppurativa, alopecia, and skin tags [7].…”
Section: Introductionmentioning
confidence: 99%
“…Molluskum pendulum lezyonlarının sistemik bir hastalığı olmayan sağ-lıklı kişilerde görülebildiği, fiziksel irritasyon sonucu oluşabildiği, ailesel geçiş özelliği gösterebildiği veya gebelikte oluşabildiği belirtilmekte olup bu konuda bir görüş birliği bulunmamaktadır. [1][2][3][4][5][6][7] Karbonhidrat metabolizması bozukluğu olan kişilerde kan şekeri yük-sekliği, insülin direnci ve dislipidemi görülebilmektedir. [8][9][10] Bu hastaların açlık kan şekeri (AKŞ), tokluk kan şekeri (TKŞ) ve insülin düzeyleri ile lipit profillerinin değerlendirilmesi gerekmektedir.…”
Section: Gi Riflunclassified
“…In diabetic patients with sign of IR, the frequencies of acrochordons and acanthosis nigricans were reported as 26.2% and 5%, respectively 7 . In many studies, conflicting results have been reported, as to the relationship among acrochordons, seborrheic keratosis, pseudoacanthosis nigricans, DM, IR and MetS, [8][9][10][11][12] and MetS components rather than the presence of MetS have been evaluated. As well as the limited number of literature including only two studies that investigated the presence of MetS in patients with acrochordons, 10,13 we also aimed at evaluating the presence of MetS in patients with acrochordons under the criteria of NCEP-ATP III.…”
mentioning
confidence: 99%
“…Since then, limited data targeting to investigate the relationship between acrochordons and the components of MetS have been published with conflicting results [8][9][10][11][12][13]18 . In a study performed by Sudy et al, 11 it was reported that eight or more acrochordons are related to basal and postprandial hyperinsulinemia and postprandial hyperglycemia, and that multiple acrochordons are more sensitive, but less specific than acanthosis nigricans in the evaluation of glucose/insulin metabolism. In the study published by Tamega et al, 12 it was also reported that acrochordons had been associated with HOMA-IR, TG, BMI, waist/ hip ratio (WHR) and the presence of DM.…”
mentioning
confidence: 99%